Electronic design: from concept to reality - Roden, Martin S (Shroff Pub, 2002)
Electronic design: from concept to reality / Roden, Martin S.. -- Kolkata: Shroff Pub., 2002 621.3815 R688e4 4th ed. No. of Copies : 1